ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MANAJEMEN LABA PADA PERBANKAN SYARIAH PERIODE 2010-2013 - Lety Puspitosari (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: Transparency in disclosing the financial statements is required by decision makers asappropriate balance and adequate information so important to the company . In the presentfinancial statements , management took accounting method with a specific purpose . This isoften referred to manajamen profit . Management actions earning management raises a numberof scandals in corporate financial reporting .In this study, a sample of Islamic banking with theobservation period 2010 to 2013. The analytical method used is multiple regression method . Theresults showed that simultaneous ( F test ) independent variables used in this study are firm size ,debt to equity ratio , return on assets , the size of the company , the audit committee and the auditof ownership has a significant effect on the occurrence of earnings management in the company .Test results on an individual basis using the t test showed that the only variable return on assetsand institutional ownership has a significant effect on the occurrence of earnings management inthe company .Keywords : Earnings Management , Profitability , Leverage , Firm Size , The Audit Committee ,Institutional Ownership